CREB3L2 Modulates Nerve Growth Factor-Induced Cell Differentiation - Sampieri, Luciana; Funes Chabán, Macarena; Di Giusto, Pablo; Rozés-Salvador, Victoria; Alvarez, Cecilia (Frontiers in Molecular Neuroscience, 2021)
Nerve growth factor (NGF) stimulates numerous cellular physiological processes, including growth, differentiation, and survival, and maintains the phenotype of several neuronal types. Most of these NGF-induced processes require adaptation of the secretory pathway since they involve extensive remodeling of membranes and protein redistribution along newly formed neuritic processes. CREB3 transcription factors have emerged as signaling hubs for the regulation of numerous genes involved in the secretory pathway and Golgi homeostasis, integrating stimuli from multiple sources to control secretion, posttranslational modifications and trafficking of proteins. Although recent studies have focused on their role in the central nervous system, little is known about their participation in cell differentiation. Therefore, we aimed to analyze the expression and signaling mechanism of CREB3 transcription factor family members, using the NGF-induced PC12 cell differentiation model. Results show that NGF treatment causes Golgi enlargement and a parallel increased expression of proteins and mRNAs encoding for proteins required for membrane transport (transport factors). Additionally, a significant increase in CREB3L2 protein and mRNA levels is detected in response to NGF. Both MAPK and cAMP signaling pathways are required for this response. Interestingly, CREB3L2 overexpression hampers the NGF-induced neurite outgrowth while its inhibition enhances the morphological changes driven by NGF. In agreement, CREB3L2 overexpressing cells display higher immunofluorescence intensity of Rab5 GTPase (a negative regulator of PC12 differentiation) than control cells. Also, Rab5 immunofluorescence levels decrease in CREB3L2-depleted cells. Taken together, our findings imply that CREB3L2 is an important downstream effector of NGF-activated pathways, leading to neuronal differentiation.